Scenario archetypes reveal risks and opportunities for global mountain futures. (July 2021) - Thorn, Jessica P.R.; Klein, Julia A.; Steger, Cara; Hopping, Kelly A.; Capitani, Claudia; Tucker, Catherine M.; Reid, Robin S.; Marchant, Robert A.
Highlights: Multiscale, systemic transformative adaptation needed in MtSES for desirable futures. Archetypes sufficiently distinct to facilitate active engagement in futures thinking. Desirable futures of conservation, income diversification, cultural heritage, tourism. Undesirable futures of land degradation, biodiversity/cultural loss, climate change. Four clusters related to wealth, inequality, temperature characterise archetypes. Abstract: Mountain social-ecological systems (MtSES) are transforming rapidly due to changes in multiple environmental and socioeconomic drivers. However, the complexity and diversity of MtSES present challenges for local communities, researchers and decision makers seeking to anticipate change and promote action towards sustainable MtSES. Participatory scenario planning can reveal potential futures and their interacting dynamics, while archetype analysis aggregates insights from site-based scenarios. We combined a systematic review of the global MtSES participatory scenarios literature and archetype analysis to identify emergent MtSES archetypal configurations. An initial sample of 1983 rendered 42 articles that contained 142 scenarios within which were 852 'futures states'. From these future states within the scenarios, we identified 59 desirable and undesirable futures that were common across studies. These 'common futures' were grouped into four clusters that correlated significantly with three social-ecological factors (GDP per capita, income inequality, and mean annual temperature). Using these clusters and their associated significant factors, we derived four MtSES scenario archetypal configurations characterized by similar key adaptation strategies, assumptions, risks, and uncertainties. We called these archetypes: (1) "revitalization through effective institutions and tourism"; (2) "local innovations in smallholder farming and forestry"; (3) "upland depopulation and increased risk of hazards"; and (4) "regulated economic and ecological prosperity". Results indicate risks to be mitigated, including biodiversity loss, ecosystem degradation, cultural heritage change, loss of connection to the land, weak leadership, market collapse, upland depopulation, increased landslides, avalanches, mudflows and rock falls, as well as climate variability and change. Transformative opportunities lie in adaptive biodiversity conservation, income diversification, adaptation to market fluxes, improving transport and irrigation infrastructure, high quality tourism and preserving traditional knowledge. Despite the uncertainties arising from global environmental changes, these archetypes support better targeting of evidence-informed actions across scales and sectors in MtSES.